2021
DOI: 10.1158/2159-8290.cd-21-0236
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Centered Interventions: The Next Breakthrough in Immuno-Oncology?

Abstract: The cancer–immune dialogue subject to immuno-oncological intervention is profoundly influenced by microenvironmental factors. Indeed, the mucosal microbiota—and more specifically, the intestinal ecosystem—influences the tone of anticancer immune responses and the clinical benefit of immunotherapy. Antibiotics blunt the efficacy of immune checkpoint inhibitors (ICI), and fecal microbial transplantation may restore responsiveness of ICI-resistant melanoma. Here, we review the yin and yang of intestinal bacteria … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 128 publications
3
108
1
1
Order By: Relevance
“…Interestingly, we identified only three patients who had received antibiotic therapy ≤14 days before the study treatment (a common exclusion criterion in clinical trials) 9 , 10 . Although existing data might suggest a diminished response to immunotherapy, each of these patients achieved a partial response 35 . Additionally, although our hypothesis is that it was the the bifidogenic properties of C. butyricum that drove the improvements in clinical outcome, one cannot rule out the possibility that changes in other species are responsible.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, we identified only three patients who had received antibiotic therapy ≤14 days before the study treatment (a common exclusion criterion in clinical trials) 9 , 10 . Although existing data might suggest a diminished response to immunotherapy, each of these patients achieved a partial response 35 . Additionally, although our hypothesis is that it was the the bifidogenic properties of C. butyricum that drove the improvements in clinical outcome, one cannot rule out the possibility that changes in other species are responsible.…”
Section: Discussionmentioning
confidence: 91%
“… 3 Accumulating evidence revealed that gut microbiota influences the response of tumors to ICB in cancer patients. 4–7 Modulation of gut microbiota has been investigated in preclinical murine tumor models and cancer patients to treat cancer. 4 , 5 , 8 , 9 Intriguingly, clinical studies have reported that manipulating the gut microbiota by fecal microbiota transplantation using stool collected from patients who had response to ICB allow advanced melanoma patients to overcome resistance to ICB.…”
Section: Introductionmentioning
confidence: 99%
“… 4–6 Some of these beneficial effects of the intestinal microbiota have been attributed to immunostimulatory metabolites generated in the host intestine (e.g., short-chain fatty acids). 7 …”
Section: Main Textmentioning
confidence: 99%
“… 27 , 28 Moreover, the fecal microbiota efficiently generates vitamin B5 from the dietary fiber component inulin, 29 and the abundance of dietary fiber has a positive impact on the outcome of immunotherapy in melanoma patients. 30 Although it is well possible that enhanced vitamin B5 levels explain this correlation, it should be noted that the microbiota may affect anticancer immunosurveillance through multiple additional effects, 7 calling for further mechanistic studies.
Figure 1.
…”
Section: Main Textmentioning
confidence: 99%